Puppies in the pantry - Baglio, Ben M.; McNicholas, Shelagh (New York : Scholastic, 1994)
At Animal Ark, Mandy Hope helps her parents treat animals of all shapes and sizes. Even outside the clinic, Mandy can't resist helping any animal in need.
"An Apple paperback."
540
Accelerated Reader AR
Keywords: Animals -- Juvenile fiction; Puppies -- Juvenile fiction; Veterinarians -- Juvenile fiction